Influence of multicultural curriculum and role models on high school students' willingness to intervene in anti-LGBTQ harassment. (October 2021) - Wernick, Laura J.; Espinoza-Kulick, Alex; Inglehart, Milo; Bolgatz, Jane; Dessel, Adrienne B.
Highlights: Exposure to curriculum on race linked with higher intervention in anti-LGBTQ behaviors. LGBTQ Curricular content not linked with higher intervention in anti-LGBTQ behaviors. Frequency of hearing anti-LGBTQ speech positively related to intervention behaviors. Overt slurs were negatively associated with likely intervention behaviors. Cisgender heterosexual girls/women reported greater intervention behaviors. Abstract: Research suggests that, through direct intervention and role modeling, student peers may be particularly well-suited to address bullying and discrimination based on gender and sexuality. To investigate the factors predicting students' self-reported intervention behaviors when witnessing harassment based on sexual orientation and gender identity, this study analyzes youth-led survey data collected at five Midwestern high schools (n = 1046). The sample was majority white (65.8%), cisgender (90.8%), and heterosexual (78.4%). We found that in addition to overall school climate and witnessing others intervene, schools having race-related curriculum significantly predicted intervention behaviors around gender and sexuality and that LGBTQ-related curricula did not predict such actions. The authors propose that the discrepancy may be due to an association between race curricula and social justice frameworks, in contrast with the emphasis on individuality and health in LGBTQ-inclusive curricula.